Cross-sectional study of Australian medical student attitudes towards older people confirms a four-factor structure and psychometric properties of the Australian Ageing Semantic Differential. Issue 8 (16th August 2020) - Wilson, Mark; Tran, Yvonne; Wilson, Ian; Kurrle, Susan E
Abstract : Objectives: The Australian Ageing Semantic Differential (AASD) survey was developed to quantify medical student attitudes towards older people. The purpose of this study is to examine psychometric properties of the survey and confirm its factor structure of four composites. Design: A cross-sectional study. Setting: Three medical schools in three Australian states: Victoria, Western Australia and South Australia. Participants: Third-year or fourth-year medical students (n=188, response rate=79%). Outcome measures: In the previous AASD study, exploratory factor analysis supported a four-factor model consisting of 'Instrumentality' (I), 'Personal Appeal' (PA), 'Experience' (E) and 'Sociability' (S). Congeneric one-factor confirmatory factor analysis (CFA) were used to examine model fit for factors using a new student sample (n=188). Psychometric properties of survey items and factors. Post-hoc analysis of pooled data from this study and earlier AASD study (n=509). Results: Indices of fit (Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), root mean square error of approximation (RMSEA), standardised root mean square residual (SRMR)) for data to the factor model were: PA adequate fit (CFI=0.94, TLI=0.89, RMSEA=0.11 and SRMR=0.05), I good fit (CFI=0.99, TLI=0.99, RMSEA=0.04 and SRMR=0.03), S good fit (CFI=0.98, TLI=0.95, RMSEA=0.06 and SRMR=0.03) and E excellent fit (CFI=1.0, TLI=1.0, RMSEA=0.00 and SRMR=0.01). The AASD was internally consistent (Cronbach's alpha=0.84), without difference in mean student scores by institution. Mean AASD score was positive for medical students outside New South Wales (73.2/114). Mean I score for all Australian students was negative, with female respondents' mean E score significantly higher than their counterparts. A positive correlation between student age and I score was noted. Conclusions: The AASD is internally consistent and generalisable within Australia, with acceptable structural validity for measuring medical student attitudes towards older people within a four-factor model. Student attitudes were positive globally and within all factors except I. Female students rated older persons E more positively. Older students recorded more positive attitudes towards I of older people.